Analisis Penerapan Profil Pelajar Pancasila SMA Negeri 1 Delitua Tahun Pelajaran 2024-2025 - Ikka Pradawati; Mimi Rosadi (Ikatan Dai Indonesia, 2025)
The Pancasila Student Profile is a reflection of Indonesian students who have strong character, have critical thinking skills, are creative, independent, and are able to work together in diversity. This concept is in line with the Strengthening of Character Education (PPK) in the 2013 Curriculum, which emphasizes the importance of forming students as individuals who are complete in terms of knowledge, attitude, and skills. This study aims to determine the extent of the implementation of the strengthening of the Pancasila Student Profile at SMA Negeri 1 Delitua. This study uses a qualitative descriptive approach with data collection techniques through interviews, questionnaires, and documentation. Data sources consist of teachers as primary data, and students and principals as secondary data that support the integrity of the information. The results of the study indicate that the implementation of the Pancasila Student Profile indicators at SMA Negeri 1 Delitua has been going quite well. Values ​​such as mutual cooperation, integrity, and noble morals are beginning to be seen in student behavior, both inside and outside the classroom. The application of holistic and contextual principles in the learning process is already apparent in daily activities at school. However, the principles of student-centered learning and explorative principles still require further strengthening so that the learning process is more meaningful. Meanwhile, the implementation of the Pancasila Student Profile strengthening project has been going well. The project activities are able to encourage students to be actively involved, collaborate, and develop their potential in accordance with the values ​​of Pancasila. However, continuous evaluation and collaboration between stakeholders are needed so that the strengthening of this profile can run consistently and have a real impact on the formation of student character.